Financial Indicators and Financial Change in Africa and Asia - Pill, Huw (IMF Working Papers; Working Paper, 1995)
Deregulation of the financial system often proceeds in tandem with macroeconomic stabilization centered on monetary and other financial targets. This paper presents a model where there may be conflict between these processes. The indicator properties of some financial variables may be rendered unstable by the liberalization process. However, other, carefully selected financial aggregates may contain information about economic activity that is useful to policy makers during stabilization. Data from a group of selected African and Asian countries is examined. These are broadly consistent with the predictions of the model, while highlighting the importance of macroeconomic and financial stability for the success of financial reforms.